Legal Transplants and the Inoculation Effect: How American Criminal Procedure has Affected Continental Europe. (1st October 2016) - Grande, Elisabetta
Abstract: This Article is a critique of the widely held idea that European criminal procedures have been "Americanized." During the last few decades, European continental criminal procedures underwent extensive reforms and the American adversary system often became the reference model for this overhaul. Nevertheless, this Article demonstrates that the transfer, rather than producing an actual diffusion of American legal institutions in Europe and making the European criminal procedure systems more adversarial, has resulted instead in its opposite— i.e., in the fortification of the non-adversary civilian structure and its tenets. It is my speculation that this occasioned what I propose to call an "inoculation effect, " which, in a Gramscian sense, is theoretically explainable as a "counterhegemonic" move. To prove my argument, I discuss the impact of some transferred features of American criminal procedure on the receiving European context. Such features, which students of legal transplants have claimed make the civilian procedures more "adversarial, " are pretrial investigations conducted by (the police and) the public prosecutor (in lieu of the investigating judge that is classical of the civilian tradition), exclusionary rules, cross-examination, and jury trial. My critique of the commonly held view shows that the imported adversarial legal arrangements were not simply "lost in translation, " i.e., reinterpreted according to the non-adversarial style of the recipient systems. To the contrary, they effectively strengthened the most essential feature of a liberal non-adversary procedure, the impartiality of a third-party official search for the truth. This is why the injection of a small portion of American adversarial procedure into the body of Continental European procedure resembles an inoculation. Indeed, just as an inoculation would do, it seems to have generated the "antibodies" able to make the latter more resistant against any future genuine Americanization, that is, against any future transplantation of an adversarial, party-controlled contest system.